Glucagon-Like Peptide-1 Inhibits Prandial Gastrointestinal Motility Through Myenteric Neuronal Mechanisms in Humans - Halim, Md Abdul; Degerblad, Marie; Sundbom, Magnus; Karlbom, Urban; Holst, Jens Juul; Webb, Dominic-Luc; Hellström, Per M (The journal of clinical endocrinology and metabolism, 2018)
Abstract Context Glucagon-like peptide-1 (GLP-1) secretion from l-cells and postprandial inhibition of gastrointestinal motility. Objective Investigate whether physiological plasma concentrations of GLP-1 inhibit human postprandial motility and determine mechanism of action of GLP-1 and analog ROSE-010 action. Design Single-blind parallel study. Setting University hospital laboratory. Participants Healthy volunteers investigated with antroduodenal manometry. Human gastric and intestinal muscle strips. Interventions Motility indices (MIs) obtained before and during GLP-1 or saline infusion. Plasma GLP-1 and glucagon-like peptide-2 (GLP-2) measured by radioimmunoassay. Gastrointestinal muscle strips investigated for GLP-1- and ROSE-010-induced relaxation employing GLP-1 and GLP-2 and their receptor localization, and blockers exendin(9-39)amide, Lω-nitro-monomethylarginine (L-NMMA), 2′,5′-dideoxyadenosine (DDA), and tetrodotoxin (TTX) to reveal target mechanism of GLP-1 action. Main Outcome Measures Postprandial gastrointestinal relaxation by GLP-1. Results In humans, food intake increased MI to 6.4 ± 0.3 (antrum), 5.7 ± 0.4 (duodenum), and 5.9 ± 0.2 (jejunum). GLP-1 administered intravenously raised plasma GLP-1, but not GLP-2. GLP-1 0.7 pmol/kg/min suppressed corresponding MI to 4.6 ± 0.2, 4.7 ± 0.4, and 5.0 ± 0.2, whereas 1.2 pmol/kg/min suppressed MI to 5.4 ± 0.2, 4.4 ± 0.3, and 5.4 ± 0.3 (P < 0.0001 to 0.005). In vitro, GLP-1 and ROSE-010 prevented contractions by bethanechol and electric field stimulation (P < 0.005 to 0.05). These effects were disinhibited by exendin(9-39)amide, L-NMMA, DDA, or TTX. GLP-1 and GLP-2 were localized to epithelial cells, GLP-1 also at myenteric neurons. GLP-1R and GLP-2R were localized at myenteric neurons but not muscle. Conclusions GLP-1 and ROSE-010 inhibit postprandial gastrointestinal motility through GLP-1R at myenteric neurons, involving nitrergic and cyclic adenosine monophosphate–dependent mechanisms. Near physiological concentrations of GLP-1 reduce prandial intestinal motility in man. GLP-1 and analogue ROSE-010 mediate responses through neuronal mechanisms requiring second messengers NO and cAMP.